An Investigation of the Use of Code-Switching in EFL Classroom: Attitudes and Perceptions - Andi Patmasari; Agussatriana; Abdul Kamaruddin (Hasanuddin University, 2022)
Despite several researches have been conducted to investigate the issue of code-switching, the findings of this research are significant as they can assist both teachers and students to consider the use of code-switching in EFL classroom, specifically in Indonesia. This research sought to investigate not only the teachers’ perceptions but also the students’ attitudes and perceptions towards the use of code-switching in EFL classroom. This research employed mixed methods research (explanatory sequential design). The participants were two teachers and forty students. Data collection instruments were the questionnaire and semi-structured interview. Findings from the teachers’ interview showed that the teachers use code-switching for certain situations and specific reasons. They emphasized that it is important to speak English as much as possible in EFL classroom because the target language is English. Furthermore, findings from the students’ questionnaire and semi-structured interview showed that most of the students have positive attitudes and perceptions towards the use of code-switching in EFL classroom. They assumed that the teacher should be allowed to use code-switching in EFL classroom since it is used for assisting students and maintaining a good communication between teacher and students.